Savonius Wind Turbine Performances on Wind Concentrator - Dygku. Asmanissa Awg. Osman; Norzanah Rosmin; Nor Shahida Hasan; Baharruddin Ishak; Aede Hatib Mustaamal@Jamal; Mariyati Marzuki (Institute of Advanced Engineering and Science, 2017)
The air streams from the outlet of an air compressor can be used to generate electricity. For instance, if a micro-sized Vertical-Axis Wind-Turbine (VAWT) is installed towards the airflow, some amount of electricity can be generated before being stored in a battery bank. The research’s objectives are to design, fabricate and analyze the performance of Helical Savonius VAWT blade rotors, which is tested with and without using a wind concentrator. The Helical Savonius VAWT is tested at 0 cm without the concentrator, whereas the blade rotor is tested at concave-blade position when using the concentrator. The blade and the wind concentrator designs were based on the dimensions and the constant airflow of the air compressor. The findings suggested that the blade produced its best performance when tested using wind concentrator at concave-blade position in terms of angular speed (ω), tip speed ratio (TSR) and the generated electrical power (PE). The findings concluded that the addition of wind concentrator increases the airflow which then provided better performances on the blades.